Comparison of the acoustic stimulation test with nonstress test. A randomized, controlled clinical trial - Tongsong T. (2014)
The nonstress test (NST) is a helpful adjunct in the management of high-risk pregnancies. It has high predictability and a low false-negative rate but unfortunately has fairly high false-positive results. Attempts have been made to find a suitable stimulant to help decrease nonreactive results as well as to shorten the duration of testing: the recently introduced fetal acoustic stimulation test (AST) may have such attributes. This prospective, randomized clinical trial was carried out to assess the new test. A total of 1,300 individual tests were performed on high-risk pregnancies. Cases were randomized to receive either the AST or NST. All tracings were interpreted blindly by an independent perinatologist. The incidence of nonreactive tests was 6.8% in the AST group and 13.8% in the NST group (P < .001). There was a significant reduction in the time needed for a reactive test to occur. It can be concluded, therefore, that AST offers a greater advantage over NST by lowering both the incidence of nonreactive tests and testing time, thereby resulting in less of a need for the contraction stress test and biophysical profile.